Modernity as a False Deity: Takfiri Anachronism in the Islamic State Group's Media Strategy. Issue 4 (2nd October 2018) - Al-Ghazzi, Omar
Abstract : This article focuses on the way the Islamic State (IS) group communicates and performs a return to the origins of Islam in seventh-century Arabia. IS performs what it imagines to be a caliphate that follows the "methodology of the Prophet"—in what represents an operationalisation of long-alluded-to Islamist rhetorical aims about a return to an Islamic authenticity and about undoing Western influences. It deems everyone who disagrees with it as simply anti-Islamic. I refer to that media strategy, which IS deploys to target its enemies as infidels, as takfiri anachronism (takfiri in Arabic is an adjective describing accusations of apostasy). I seek to demonstrate how IS's takfiri anachronism relies on mixed discursive textual and visual tactics that aim to conceal its contemporary political hybridity, vulnerability and its presentist approach to Islamic texts. I analyze IS's self-presentation as a caliphate in a number of its official videos and statements. I focus on the initial IS announcement on the establishment of the caliphate and how its leader Abu-Bakr Al-Baghdadi performed his role as "the caliph" in the summer of 2014. I also examine how the parallelism between its videos showing the destruction of the Iraqi-Syrian common border, and its videos displaying the destruction of pre-Islamic archeological monuments, presents an absolute binary between the categories of "Muslim" and "infidel, " which is projected across time.